The Edinburgh Postnatal Depression Scale: translation and validation for a Greek sample - Kogevinas Manolis; Dafermos Vassilis; Vivilaki Victoria G; Bitsios Panos; Lionis Christos (BMC, 2009)
Abstract Background Edinburgh Postnatal Depression Scale (EPDS) is an important screening instrument that is used routinely with mothers during the postpartum period for early identification of postnatal depression. The purpose of this study was to validate the Greek version of EPDS along with sensitivity, specificity and predictive values. Methods 120 mothers within 12 weeks postpartum were recruited from the perinatal care registers of the Maternity Departments of 4 Hospitals of Heraklion municipality, Greece. EPDS and Beck Depression Inventory-II (BDI-II) surveys were administered in random order to the mothers. Each mother was diagnosed with depression according to the validated Greek version of BDI-II. The psychometric measurements that were performed included: two independent samples t-tests, One-way analysis of variance (ANOVA), reliability coefficients, Explanatory factor analysis using a Varimax rotation and Principal Components Method. Confirmatory analysis -known as structural equation modelling- of principal components was conducted by LISREL (Linear Structural Relations). A receiver operating characteristic (ROC) analysis was carried out to evaluate the global functioning of the scale. Results 8 (6.7%) of the mothers were diagnosed with major postnatal depression, 14 (11.7%) with moderate and 38 (31.7%) with mild depression on the basis of BDI-II scores. The internal consistency of the EPDS Greek version -using Chronbach's alpha coefficient- was found 0.804 and that of Guttman split-half coefficient 0.742. Our findings confirm the multidimensionality of EPDS, demonstrating a two-factor structure which contained subscales reflecting depressive symptoms and anxiety. The Confirmatory Factor analysis demonstrated that the two factor model offered a very good fit to our data. The area under ROC curve AUC was found 0.7470 and the logistic estimate for the threshold score of 8/9 fitted the model sensitivity at 76.7% and model specificity at 68.3%. Conclusion Our data confirm the validity of the Greek version of the EPDS in identifying postnatal depression. The Greek EPDS scale could be used as a useful instrument in both clinical practice and research.